Water-triggered microphase reconstruction enables anti-swelling ion transport in amphiphilic ionogels for adaptive multimodal sensing - Yu Zhang; Ruobing Tian; Xueming Tang; Zengguang Ji; Jiahao Liu; Xinli Wang; Guojun Deng; Bin Miao; Yuanna Sun; Hongyang Chen; Yongxing Wang (Chemical Engineering Journal, 2026)

Evaluating the efficacy of China's emission reduction policies on air quality and health: A novel spatiotemporally-resolved weather-normalization approach - Yuchao Ren; Tong Wu; Yangchun Yu; Yanbo Peng; Qingzhu Zhang; Chenliang Tao; Ruobei Zhao; Shuping Ji; Ruobing Liu; Zhenyu Gao; Qiao Wang; Wenxing Wang (Atmospheric Environment, 2026)

A novel E-type hollow silica nanosphere Enabling transparent radiative cooling coatings for light and thermal management of glass - Ruobing Yu; Shijie Zhang (Energy and Buildings, 2026)

Amino acid functionalization-induced dipole regulation suppresses carrier decay in perylene diimide to enhance photocatalytic activity - Weili Yu; Ningjie Fang; Ruobing Wang; Zhaobing Liu; Jinhui Li; Jieyuan Li; Hongxiang Li; Heng Wang; Jie Xiong; Yinghao Chu (Journal of Hazardous Materials, 2026)

Heat-modulated brown rice starch-protein: Physicochemical, functional, and digestibility properties - Ruobing Yu; Yujie Deng; Ying Wan; Xinyan Zhan; Dongjian Dai; Fei Yan; Zhihua Dai; Dan Ouyang; Jiali Xing; Xiaohu Luo (Journal of Food Engineering, 2026)

pH-tuned hydrothermal synthesis of sludge-derived biochar for enhanced activation of peroxymonosulfate in tetracycline degradation - Zhaobing Liu; Weili Yu; Xiaoxia Yang; Ruobing Wang; Ningjie Fang; Haiqing Chang; Ye Du; Yinghao Chu (Journal of Cleaner Production, 2026)

Multi-stage evolution of sandstone properties during CO2 sequestration: Mechanisms and implications - Yonggang Ding; Lyu Qiao; Ruobing Luo; Guodong Han; Xin Liu; Bingbin Xie; Jia Yu; Jingqiang Tan (Gas Science and Engineering, 2026)

Fe-Cu bimetallic synergy: Elucidating the mechanism and enhanced efficiency of sludge-based biochar in activating PMS - Zhaobing Liu; Ruobing Wang; Chuanfan Yang; Ningjie Fang; Weili Yu; Juan Liang; Yinghao Chu (Biomass and Bioenergy, 2026)

Pollutant-specific reactive species fingerprints: elucidating differential photocatalytic antibiotic degradation mechanisms in ZnIn2S4-based systems - Ruobing Wang; Zhaobing Liu; Weili Yu; Ningjie Fang; Jinhui Li; Yinghao Chu (Journal of Environmental Management, 2026)

Microphase separation-induced conductivity enhancement in anti-swelling amphiphilic ionogels for multimodal sensing - Xueming Tang; Jiahao Liu; Ruobing Tian; Yu Zhang; Xinli Wang; Lei Zhang; Zhaoqing Li; Jianlin Yuan; Yan Jiang; Yuanna Sun (Chemical Engineering Journal, 2026)

CO2-responsive gels for enhanced oil recovery and carbon sequestration: A comprehensive review of design and applications - Jianing Yu; Xu Li; Ruobing Qiao; Liming Zheng; Nasir Khan; Haifeng He; Zhimin Peng; Yanhua Yu (Journal of Environmental Chemical Engineering, 2025)

Synergistic and continuous driving of Fe(III)/Fe(II) cycle by electron-rich organic contaminants and peroxymonosulfate: Homogeneous feasibility and heterogeneous application - Jin Chai; Yu Wei; Haoran Kong; Hui Liu; Zhuohan Li; Junshuo Huang; Ruobing Pi; Zhe Yang; Xuhui Sun (Chemical Engineering Journal, 2025)

Vapor-phase polymerization of polypyrrole in PVA hydrogels for enhanced electrical conductivity in multimodal sensing applications - Ruobing Tian; Yu Zhang; Yuanna Sun; Jiahao Liu; Xueming Tang; Jinlong Gao; Guixin Lv; Yan Jiang; Jun Fu (Chemical Engineering Journal, 2025)

A review of the extraction technologies, structural characterization, chemical modification, and pharmacological effects of Ganoderma lucidum polysaccharides - ChenXue Li; RuoBing Zhang; Bing Tian; Bing Liu; Yu Mei; WenLan Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Galvanic effects between mackinawite and pyrogenic carbon: Enhancing radical-mediated ciprofloxacin transformation - Danning Lu; Longgang Chu; Haoran Yu; Zhaoyue Sun; Xiru Chen; Ruobing Wang; Xing Liu; Zhanghao Chen; Juan Gao; Cheng Gu (Journal of Hazardous Materials, 2025)

Multi-omics insights into 6PPD- and 6PPDQ-induced gut-liver axis disruption and non-alcoholic fatty liver disease progression in zebrafish (Danio rerio) - Yu Feng; Hongyi Xian; Ruobing Bai; Zhiming Li; Hao Li; Long Zhang; Xiyun Huang; Yuji Huang; Boxuan Liang; Yanhong Deng; Xiaohong Yang; Xiaoqing Chen; et al. (Journal of Hazardous Materials, 2025)

Sequential heterotrophy–dilution–photoinduction cultivation of Botryococcus sudeticus for enhanced squalene production - Ruobing Tan; Tao Yu; Lulu Yan; Weiliang Wang; Minxi Wan; Yuanguang Li (Algal Research, 2025)

Electroporation optimization for cell wall-deficient and cell-walled Chlamydomonas reinhardtii using response surface methodology - Minxi Wan; Ruobing Tan; Zining Wang; Weiliang Wang; Tao Yu; Yuanguang Li (Algal Research, 2025)

Continuous treatment of contaminants through activation of peroxymonosulfate utilizing ferrate-modified graphite felt: Radical and non-radical - Zhe Yang; Jin Chai; Yu Wei; Ruobing Pi; Siyang Wang; Xuhui Sun (Journal of Water Process Engineering, 2025)

Investigation on the influence mechanism of N element doping on the photocatalytic properties of the g-C3N4@ZnCdS composite photocatalyst - Fucheng Yu; Ruobing Jiang; Xuying Duan; Jielin Zhang; Jinlong Ren; Chenchen Feng; Cuixia Li; Kechao Hu; Xiaogang Hou (Journal of Water Process Engineering, 2025)

Gender-specific effects of polystyrene nanoplastic exposure on triclosan-induced reproductive toxicity in zebrafish (Danio rerio) - Zhiming Li; Hongyi Xian; Rongyi Ye; Yizhou Zhong; Boxuan Liang; Yuji Huang; Mingzhu Dai; Jie Guo; Shuqin Tang; Xiaohu Ren; Ruobing Bai; Yu Feng; et al. (Science of The Total Environment, 2024)

From cradle to grave: Deciphering sex-specific disruptions of the nervous and reproductive systems through interactions of 4-methylbenzylidene camphor and nanoplastics in adult zebrafish - Hongyi Xian; Zhiming Li; Ruobing Bai; Rongyi Ye; Yu Feng; Yizhou Zhong; Boxuan Liang; Yuji Huang; Jie Guo; Binjie Wang; Mingzhu Dai; Shuqin Tang; et al. (Journal of Hazardous Materials, 2024)

The structural and functional properties of a novel enzyme-modified starch as an alternative to hydroxypropyl starch ether - Ruobing Li; Haiteng Tao; Congping Tan; Fang Yuan; Li Guo; Bo Cui; Yu Zhu; Feixue Zou; Pengfei Liu; Lu Lu (Food Hydrocolloids, 2024)

Investigation of the catalytic effect of defective Ni-MOF-74 on polymerization of dopamine and multi-pore polydopamine photothermal coating constructed with defective Ni-MOF-74 particles - Yiguan Wang; Ruobing Yu (Journal of Environmental Chemical Engineering, 2023)

4-Methylbenzylidene camphor triggers estrogenic effects via the brain-liver-gonad axis in zebrafish larvae - Hongyi Xian; Zhiming Li; Rongyi Ye; Mingzhu Dai; Yu Feng; Ruobing Bai; Jie Guo; Xiliang Yan; Xingfen Yang; Da Chen; Zhenlie Huang (Environmental Pollution, 2023)

Construction of BiOCl/Ti-MOFs type-II heterojunction photocatalyst for enhanced photocatalytic performance for multiple antibiotics removal - Chengwei Wang; Zhuhuan Chen; Ruobing Yu (Environmental Science and Pollution Research, 2023)

A Nonlinear Model and Parameter Identification Method for Rubber Isolators under Shock Excitation in Underwater Vehicles - Heye Xiao; Chizhen Xu; Ruobing Wang; Peixun Yu; Jie Zhou; Junqiang Bai (Journal of Marine Science and Engineering, 2021)
Rubber isolators are usually used to protect high-precision equipment of autonomous underwater vehicles (AUVs), avoiding damage from overlarge dynamic excitation. Considering the nonlinear properties of the rubber material, the nonlinear behavior of rubber isolators under shock exaltation is hard to be predict accurately without the available modal and accurate parameters. In view of this, the present study proposes a nonlinear model and parameter identification method of rubber isolators to present their transient responses under shock excitation. First, a nonlinear model of rubber isolators is introduced for simulating their amplitude and frequency-dependent deformation under shock excitation. A corresponding dynamic equation of the isolation system is proposed and analytically solved by the Newmark method and the Newton-arithmetic mean method. Secondly, a multilayer feed-forward neural network (MFFNN) is constructed with the current model to search the parameters, in which the differences between the estimated and tested responses are minimized. The sine-sweep and drop test are planned with MFFNN to build the parameter identification process of rubber isolators. Then, a T-shaped isolator composed of high-damping silicon rubber is selected as a sample, and its parameters were determined by the current identification process. The transient responses of the isolation system are reconstructed by the current mode with the identified parameter, which show good agreement with measured responses. The accuracy of the proposed model and parameter identification method is proved. Finally, the errors between the reconstructed responses and tested responses are analyzed, and the main mode of energy attenuation in the rubber isolator is discussed in order to provide an inside view of the current model.

Levels of Perfluoroalkyl Acids (PFAAs) in Human Serum, Hair and Nails in Guangdong Province, China: Implications for Exploring the Ideal Bio-Indicator - Baolin Liu; Ruobing Zhang; Hong Zhang; Yong Yu; Dan Yao; Shaoqiang Yin (Archives of Environmental Contamination and Toxicology, 2020)

Isolation of fourteen novel polymorphic microsatellite markers for alien or invasive species: monitoring and management of the mud snail Bullacta exarata Philippi, 1849 - Xiaoying Li; Yu Leng; Zhiguo Dong; Yiting Liu; Ruobing Wen; Xudong Liu; Peiming He (Conservation Genetics Resources, 2014)